The Effect of Work Discipline, Work Motivation, And Work Environment on The Performance of Contract Employees In The Environmental Service of Gresik Regency - Hidayati, Roziana Ainul; Itidiyati, Dia Sitni (Universitas Muhammadiyah Gresik, 2025)
This research aims to determine the influence of work discipline, work motivation, and work environment on the performance of Gresik district environmental service employees. This research is included in the category of causal associative research using a quantitative approach. The sampling technique in this research uses the Non-Probability Sampling technique with saturated sampling, namely the sampling technique when all members of the population are used as samples. This is often done when the population is relatively small, or the research wants to make generalizations with very small errors. Another term for a saturated sample is a census, where all members of the population are sampled, the data source is 110 employees. The data analysis technique uses multiple linear regression. The results of multiple linear regression analysis prove that work discipline, motivation and work environment are proven to have a partially significant influence on the performance of Gresik district environmental service employees. These results can be interpreted that the existence of work discipline, motivation and work environment can improve the performance of Gresik district environmental service employees.